2015
DOI: 10.1016/j.ijms.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

New approach for studying slow fragmentation kinetics in FT-ICR: Surface-induced dissociation combined with resonant ejection

Abstract: A B S T R A C TWe introduce a new approach for studying the kinetics of large ion fragmentation in the gas phase by coupling surface-induced dissociation (SID) in a Fourier transform ion cyclotron resonance mass spectrometer with resonant ejection of selected fragment ions using a relatively short (5 ms) ejection pulse. The approach is demonstrated for singly protonated angiotensin III ions excited by collisions with a self-assembled monolayer of alkylthiol on gold (HSAM). The overall decomposition rate and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 67 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Resonant ejection was performed by applying an excitation pulse of t 1 ms duration at the resonant frequency of a fragment ion of interest to the two excitation plates of the ICR cell 6 ring electrode. [42] In this study, SID spectra were acquired at 15 delay times between ion trapping and resonant ejection given by equation (1): (1) with the shortest delay time placing the ejection pulse right before ion trapping and the longest delay time of 179 ms. This allowed access to both fast and slow fragmentation pathways.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Resonant ejection was performed by applying an excitation pulse of t 1 ms duration at the resonant frequency of a fragment ion of interest to the two excitation plates of the ICR cell 6 ring electrode. [42] In this study, SID spectra were acquired at 15 delay times between ion trapping and resonant ejection given by equation (1): (1) with the shortest delay time placing the ejection pulse right before ion trapping and the longest delay time of 179 ms. This allowed access to both fast and slow fragmentation pathways.…”
Section: Methodsmentioning
confidence: 99%
“…[18,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Another approach for studying the kinetics of large ion fragmentation combines SID in a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS) with resonant ejection of selected fragment ions at a variable delay time. [42] In this approach, fragment ions at a particular m/z formed before the ejection pulse is applied are removed from the spectrum, while ions at the same m/z formed after the ejection pulse are detected in the spectrum. In addition, product ions formed through sequential fragmentation of the ejected fragment are affected by the ejection pulse, while all other fragments remain unperturbed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SID in FT-ICR-MS provides several advantages for studying energy and entropy effects in the dissociation of large ions 19 influenced by the presence of a kinetic shift. 41 These include the efficient collection of scattered ions in a strong magnetic field, a long and variable delay time between the ion-surface collision and the analysis that facilitates time-resolved SID studies, 40 and resonant ejection of selected fragment ions, recently used for studying the kinetics and mechanisms of peptide fragmentation in the gas phase on a timescale of >1 ms. 42 Furthermore, it has been demonstrated that small changes in dissociation parameters are efficiently amplified in FT-ICR-MS SID experiments. 19 This "amplification" originates from differences in kinetic shifts that are substantial for slow fragmentation pathways and from partial conversion of the projectile ion's kinetic energy into the vibrational excitation.…”
Section: Introductionmentioning
confidence: 99%